2023
DOI: 10.3390/jcm12082978
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Treatment and Outcomes of High Surgical Risk Mitral Regurgitation

Abstract: Before the development of transcatheter interventions, patients with mitral regurgitation (MR) and high surgical risk were often conservatively treated and subject to poor prognoses. We aimed to assess the therapeutic approaches and outcomes in the contemporary era. The study participants were consecutive high-risk MR patients from April 2019 to October 2021. Among the 305 patients analyzed, 274 (89.8%) underwent mitral valve interventions, whereas 31 (10.2%) received medical therapy alone. Of the intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…[ 50 ] Sudo et al reported that percutaneous MV intervention (TEER or transcatheter MV replacement [TMVR]) decreases HF hospitalisations and improves NYHA class functional status more effectively compared to medical treatment alone. [ 51 ]…”
Section: Left Atrial Function and Transcatheter Edge-to- Edge Repair ...mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 50 ] Sudo et al reported that percutaneous MV intervention (TEER or transcatheter MV replacement [TMVR]) decreases HF hospitalisations and improves NYHA class functional status more effectively compared to medical treatment alone. [ 51 ]…”
Section: Left Atrial Function and Transcatheter Edge-to- Edge Repair ...mentioning
confidence: 99%
“…Recently, a risk model has been introduced to predict outcomes after surgery in PMR patients. [ 51 ] Maybe it is time to let artificial intelligence guide us in decision-making for SMR intervention by using an equivalent model that will take several clinical and echocardiographic factors into account.…”
Section: Clinical Implications and Future Perspectivesmentioning
confidence: 99%